Perancangan Model Indeks Prestasi dan Masa Studi Terbobot Pada Universitas Pattimura Ambon - N. E. Maitimu (ARIKA, 2012)
The quality of education is the objective of every education institusion in order to be acknowledge by their outcome users. That is the reason that University of Pattimura tries to improve their quality assurance of education and duration of study. These have programmed for every student to finish their study on time according to curriculum with a satisfactory grade point. The university proposes Indeks Prestasi Masa Studi Terbobot method to describe the most qualified serviceable faculty, department or study program in accordance with vision dan mission of the university. A research is developed to analyze students performance on 8 faculties, 21 departments, and 50 study programs by calculating student-s grade point dan study duration of study base on graduated book of every graduation period.